Effect of arbuscular mycorrhizal symbiosis on grapevine response to Neofusicoccum parvum, a major trunk disease fungus - Lorène Belval; Lucie Roth; Isabelle R. Martin; Hélène Laloue; Laurence Deglene-Benbrahim; Laure Valat; Mary-Lorène Goddard; Julie Chong (Plant Stress, 2024)
Grapevine is an economically-important culture worldwide but is currently the target of decline, especially caused by grapevine trunk diseases (GTD). One of the major grapevine trunk disease is Botryosphaeria dieback, which is associated with Botryosphaeriaceae fungi. Among the different methods that could contribute to increase grapevine fitness under stresses, viticulture could take advantage of symbiosis with arbuscular mycorrhizal fungi. Within this context, we investigated the effect of V. vinifera cv. Gewurztraminer colonization with the arbuscular mycorrhizal fungus Rhizophagus irregularis on plant tolerance to wood inoculation with Neofusicoccum parvum Bt67, one of the most aggressive fungus associated with Botryosphaeria dieback. We showed that grapevine mycorrhization resulted in a small but significant reduction of wood necrosis size and less intense necrosis symptoms on the leaves. We further characterized the response of grapevine leaves and roots to both arbuscular mycorrhizal fungus (AMF) symbiosis and GTD fungus inoculation, especially the interaction between these two conditions, with a non-targeted metabolomic approach. In the roots, both mycorrhization and N. parvum infection triggered metabolite reprogramming, especially sugars and stilbenes, which were downregulated by both AMF symbiosis and pathogen infection. Furthermore, N. parvum infection triggered a significant decrease in fatty acids and oxylipins in leaves of non-mycorrhized plants, whereas contents were maintained or increased in Rhizophagus irregularis-colonized plants. In conclusion, AMF symbiosis may be an interesting tool to improve health of young grapevines and help sustaining infection by trunk disease fungi, by harnessing lipid metabolism.